Efeito do exercício resistido na cartilagem articular de modelo animal de osteoartrite - Vasilceac, Fernando Augusto (2012)
The aim of this study was to evaluate the effect of a strength exercise protocol on articular cartilage in animal model of osteoarthritis (OA). Thirty-six rats were divided in 6 groups: Control (C, n = 6), Osteoarthritis (OA, n = 6), Sham (S, n = 6), Control with exercise (E n = 6), Osteoarthritis with exercise (OAE, n = 6) and Sham with exercise (SE, n = 6). The animal model of osteoarthritis was anterior cruciate ligament transection (ACLT) in rats. After 2 weeks of ACLT, groups E, OAE and SE started the strength exercise protocol, three times a week for 8 weeks. We used the Mankin Histologic Grading System, measured the density of chondrocytes, the density of collagen fibers and the expression of collagen type II, chondroitin sulfate and fibronectin. The groups subjected to strength exercise protocol, OAE and SE, had lower values for the Mankin score, chondrocyte density and fibronectin expression and higher values for collagen fibers density, type II collagen expression and chondroitin sulfate expression when compared with OA and S, respectively. Group E was different from group C only in chondrocyte density and fibronectin expression. Therefore, strength exercise changes the content and expression of different articular cartilage constituent, having influence on our animal model of osteoarthritis and provides benefits to the cartilaginous tissue.